Comparison of hCG Versus Gonadotropin-Releasing Hormone Agonist to Induce Oocyte Maturation in Assisted Reproductive Technology Cycles: A Retrospective Cohort Study - Nacak, Gulay Beydilli; Tozkir, Elif; Ozkaya, Enis; Cogendez, Ebru; Kaya, Fatih (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: To compare some cycle characteristics and outcomes using a protocol consisting of a GnRH agonist trigger or hCG trigger after cotreatment with GnRH antagonist. STUDY DESIGN: Thirty-three patients under 35 years of age with polycystic ovarian syndrome, polycystic ovarian morphology, or previous high response who underwent ovulation trigger by GnRH agonist trigger and 132 patients under 35 years of age with the polycystic ovarian syndrome, polycystic ovarian morphology, or previous high response who underwent ovulation trigger by hCG for IVF treatment. Patients were non-randomly assigned to an ovarian stimulation protocol consisting of either GnRH agonist trigger after cotreatment with GnRH antagonist (study group) or hCG trigger after antagonist protocol (control group). RESULTS: The positive pregnancy test was obtained in 70 women in the control group whereas in 13 cases in the study group (p=0.161). No case in the study group needed hospitalization whereas there were 15 cases in the control group who were required to be hospitalized due to ovarian hyperstimulation related symptoms (p=0.04). CONCLUSIONS: The use of a protocol consisting of a GnRH agonist trigger after GnRH antagonist cotreatment and freeze-all strategy reduces the risk of ovarian hyperstimulation syndrome in high-risk patients undergoing IVF without affecting pregnancy rates.